Breaking the Carbon Lock-In Effect in Post-disaster Rebuilding: A Case Study of a Wenchuan Earthquake-Stricken City in China - Jiang Wei (Comparative Southeast European Studies)
While post-disaster rebuilding is an urgent task for affected areas, an approach without consideration for climate protection will probably lead to another disaster of carbon lock-in. Therefore, policymaking and implementation are critically important. This paper takes the Guangyuan prefecture as a case study, where the local government took the lead in low-carbon initiative and made a great contribution to low-carbon development. Based on long-term field investigations and semi-structured interviews, using the theory of multi-level governance, it discusses policy formation and implementation in the Guangyuan prefecture, and how the governance system promoted an environment-and-climate-friendly rebuilding. The results demonstrate the urgency of carbon decoupling in post-disaster-rebuilding and the significance of an effective governance system. This provides insight to the contemporary world that post-disaster rebuilding is not only a revitalization of the affected areas, but a comprehensive undertaking to avoid other possible disasters and ensure a sustainable future.